Histopathological and Stereological Study of the Effects of Gallic Acid Administration on Hippocampal Neuronal Density after Trimethyltin Toxication - heydar aqababa; Mona Ghezelbash; Mohamad Amin Edalatmanesh; Shirin Dehghan (Islamic Azad University, 2018)
Introduction: Trimethyltin is a methylated organotin, which induces selective damage and neuronal death in human and rodents' CNS. On the other hand, the neuroprotective effects of Gallic acid can prevent toxicity of trimethyltin. In the current study, the repairing effect of Gallic acid in cell injury caused by trimethyltin in rats was evaluated. Also, this study assessed the effects of Gallic acid on neuronal density of the different hippocampal areas of intoxicated rats with trimethyltin. Methods: 30 rats were divided in three groups: the no treatment control group, the control group, and the experimental group with intraperitoneal injection of trimethyltin (8 mg/kg) and Gallic acid solvent for 14 days. In the experimental group, after the administration of trimethyltin, 50 mg/kg of Gallic acid was injected. It was continued for 14 days. Finally, the rats were killed with transcardial perfusion. Histopathological and stereological analysis was performed on the rats. In this research, Kolmogorov-Smirnov test, one-way analysis of variance, and Tukey's post-hoc test were used. Results: The results of this study showed that neuronal density of different hippocampal areas of the no treatment control group was significantly increased compared to the rats of the control and experimental groups (P<0.05), while chronic administration of Gallic acid could prevent apoptosis and protect hippocampal cells. Conclusions: According to the results, it is suggested that chronic administration of Gallic acid decreases the effects of trimethyltin and therefore, it prevents the reduction of hippocampal cells.